Pengaruh Online Customer Review Dan E-Service Quality Terhadap Keputusan Pembelian Produk Fashion Di Marketplace Shopee (Studi Kasus Pada Mahasiswa Institut Stiami Kota Bekasi Angkatan 2019) - Nurbaiti, Dewi; Afriana, Irna (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The ongoing phenomenon of online shopping necessitates business entities to pay attention to customer reviews (Online Customer Review) and provide top-notch electronic services (E- Service Quality) to enhance customer decisions when purchasing fashion products on marketplace platforms. Shopee is one such platform of focus in this study. The research aims to assess the influence of online customer reviews and e-service quality on the decision-making process for purchasing fashion products on the Shopee Marketplace, as well as their combined impact. This case study involves students from the 2019 cohort at STIAMI Institute, Bekasi. The methodology employed is quantitative. The population consists of students from the 2019 cohort at STIAMI Institute, Bekasi, who have used the Shopee app for online shopping. A descriptive approach with questionnaire distribution is utilized as the data collection technique. Data analysis involves instrument testing, classical assumption testing, multiple linear regression, and hypothesis testing. The research findings indicate that both online customer reviews and e-service quality significantly influence the decision to purchase fashion products on the Shopee Marketplace, as evidenced by partial testing. Simultaneously, online customer reviews and e- service quality collectively have an impact on the decision-making process for purchasing fashion products on the Shopee Marketplace.